A Unified Modeling Scheme of Modular Multilevel Converter for Hybrid AC/DC Power Grids - Xie, Xingfeng; Wu, Zaijun; Hu, Qinran; Quan, Xiangjun; Dou, Xiaobo; Cao, Xiaoyong (Frontiers in Energy Research, 2022)
Modular multilevel converters (MMCs), as one of the core components of hybrid AC/DC power grids, become the preferred converter topology and show good developments. Urgently, a general MMC modeling scheme with good model accuracy needs to be developed to realize small-signal analyses and designs for the large-scale AC/DC power grids easily. This paper proposes a unified modeling scheme (UMS) for MMC systems in a synchronous rotating (dq) reference frame. Based on the dynamic phasor theory and with the proposed modular decouple modeling (MDM), the nonlinear state-space model of the overall MMC system can be obtained by configuring and connecting the input and output of the state-space model of each subsystem. Besides, the unified controller, modeling different control modes, normalizes the MMC systems modeling. Simultaneously, with the proposal of UMS, linearization and splicing could be uesd to develop a small-signal model of the overall MMC system directly. Therefore, the proposed model is suitable for simulating the large-scale hybrid AC/DC power grids and analyzing the stability of small-signal. Finally, the simulation results verify the accuracy and effectiveness of the proposed modeling method.